Restorative Justice And As-Ṣulhu In Islamic Law: A Maqaṣid Sharia Perspective On Criminal Justice Reform In Indonesia - Hasna Afifah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) replaces the Dutch colonial legacy of the Criminal Code, which served as the basis for material law. Formal legal reform is also crucial to create harmony in law enforcement. The reform of criminal law in Indonesia demonstrates a new direction by using a more restorative and humanistic approach, not solely emphasizing the aspect of retaliation. One of the materials of the Criminal Code reform is the concept of restorative justice, which in Arabic is called as-sulhu (peace/reconciliation). In Islamic law, as-sulhu is an alternative dispute resolution by producing a peaceful agreement between the two parties, this is in line with the values of restorative justice adopted in criminal law. This article aims to examine the relevance of the concept of as-sulhu in criminal law reform from the perspective of maqasid sharia. This study uses normative methods and a conceptual approach to examine the new Criminal Code, utilizing the theory of maqasid Sharia as an analytical tool. The results explain that the concept of restorative justice aligns with the principles of as-ulhu in Islamic law, which prioritizes public welfare. Within the national Criminal Code, there is an opportunity to integrate the values of as-ulhu through a restorative justice approach. This study also emphasizes the urgency of the relevance of sharia values to the national legal system, both of which aim to realize substantive justice that is responsive to religious and socio-cultural values for Indonesian society